Rule of experts : Egypt, techno-politics, modernity - Mitchell, Timothy, 1955- (University of California Press, 2002)
In a series of interrelated essays focused on twentieth-century Egypt, the author, a political theorist, provides an examination of the forms of reason, power and expertise that characterize contemporary politics.
Parts of the text previously published.
Keywords: Egypt -- Economic policy.; Peasants -- Egypt -- History -- 20th century.; Egypt -- Economic conditions -- 1919-1952.; Egypt -- Economic conditions -- 1952-; Egypt -- Politics and government -- 20th century.; Paysannerie -- Égypte -- Histoire -- 20e siècle.; Égypte -- Politique économique.; Égypte -- Conditions économiques -- 1919-1952.; Égypte -- Conditions économiques -- 1952-; Égypte -- Politique et gouvernement -- 20e siècle.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; HISTORY -- Middle East -- General.; Politics and government; Economic history; Economic policy; Peasants; Egypt; Wirtschaftspolitik; Moderne; Ägypten; Politieke situatie.; Egypte.; Paysannerie -- Égypte -- 20e siècle.; Égypte -- Conditions économiques -- 20e siècle.; Since 1900; History